“The worst is when you peel it and see that there is a worm”: A network semantic analysis of online reactions following Control Portugal’s controversial Instagram post - Santos, R. B.; Costa, B. F.; Oliveira, H. G. (Journal of Media Ethics)
This study analyzes the followers’ reactions to Control Portugal, which removed a humorous post from its Instagram page within hours after it was perceived by the public as transphobic. Semantic network analysis was used to identify key themes and discourse patterns in 9384 comments. The findings show that the brand’s distinctive authenticity split public opinion. Some users found the post offensive, whereas others viewed its removal as an act of censorship. After the official apology, the brand’s calculated return to humor and authenticity helped stabilize the conversation in parts of the network, easing the initial polarization. The case study thus highlights the importance of brands designing communication strategies that combine creativity with social responsibility and that ensure digital brand management not only mobilizes but also respects ethical principles.